Rethinking the divide: Exploring the interdependence between global and nested local markets. (April 2021) - Olofsson, Malin; Ros-Tonen, Mirjam; Gupta, Joyeeta; de Steenhuijsen Piters, Bart; Van Leynseele, Yves
Abstract: The debate on smallholder commodification trajectories tends to be polarised between mainstream approaches that advocate tighter integration of smallholders into global value chains, and alternative approaches that favour localised markets on the grounds that these provide greater autonomy over production and marketing, and allow a greater share of value to be realised for producers and the wider community. This debate obscures the interrelations and possible synergies between them; a critique taken up in this paper. Using a case study on agricultural diversification in the former homeland of Venda, South Africa, we explore the usefulness of the nested markets concept to make sense of smallholders' patterning of markets by combining tree crops for export with seasonal vegetables for local markets. Exploring the drivers of diversification, we show how farmers' patterning of markets depends on their profiles and corresponding trajectory of accumulation. Local markets are articulated systems that function as hybrid spaces of interaction that enable farmers without any alternative off-farm income to gain and sustain access to global commodity markets. This challenges the framing of nested markets as an act of resistance as well as the dichotomy between local versus global markets as mutually exclusive. Instead, we argue that these markets can be interconnected and mutually supportive and are opportunistically used as such by petty commodity producers to sustain their export-oriented production system. If these relations are better understood, they stand to enable agrarian policy, which currently favours high-value tree crops, to be more inclusive of young and less well-resourced farmers. Highlights: Dichotomizing local and global markets is problematic. Local nested markets can enable, sustain and complement access to high-value export markets. Farmers combine local and global markets depending on their accumulation trajectory. Local nested markets are important for smallholders without off-farm income. Operating in nested markets is not necessarily an act of resistance.